A Systematic Review of the Associations of Adult Sexual Abuse in Women with Cardiovascular Diseases and Selected Risk Factors - Nasheeta Peer; Naeemah Abrahams; Andre-Pascal Kengne (Ubiquity Press, 2020)
Aim: To systematically assess the association between adult sexual abuse (ASA) and cardiovascular diseases (CVDs) of heart attack and stroke, and their risk factors of hypertension, diabetes, dyslipidaemia and obesity. Methods: Two authors conducted a PubMed, Scopus and Web of Science review of the literature published prior to 1 October 2019. Relevant English language studies irrespective of study design and data collection techniques were included. Included articles needed to have examined ASA per se independent of physical or psychological/emotional abuse, and childhood sexual abuse. Results: Of the 3260 articles identified, nine were selected from 97 full-text articles assessed for eligibility (n = 855 206 women). Six studies were cross-sectional in design while three articles were from longitudinal studies; all emanated from the United States. One study only (n = 867) performed clinical assessments (heights and weights) to determine the relevant outcome (obesity), four presented self-reported outcomes (heart attack, stroke, hypertension, diabetes, obesity), two reviewed clinical records and two did not provide details on outcome assessments (obesity). Sexual abuse by an intimate partner was examined in five articles, three assessed military sexual trauma and a single study evaluated any perpetrator. A meta-analysis could not be conducted because of the heterogeneity across studies. The available evidence was insufficient to quantify the relationship, if any, between ASA and CVDs and their risk factors. Conclusions: Currently, no longitudinal studies of ASA in general populations have objectively investigated the development of CVDs and their risk factors using clinical and biochemical measurements. In view of the high CVD burden, and the frequency of ASA, it is important to fully understand the relationship between the two.